Diagnostic accuracy of lung ultrasound for identification of elevated left ventricular filling pressure. (15th April 2019) - Hubert, Arnaud; Girerd, Nicolas; Le Breton, Hervé; Galli, Elena; Latar, Ichraq; Fournet, Maxime; Mabo, Philippe; Schnell, Frederic; Leclercq, Christophe; Donal, Erwan
Abstract: Aims: The current algorithm in transthoracic echocardiography (TTE) proposed in the 2016 ASE/EACVI recommendation for the estimation of left ventricular filling pressure (LVFP) is quite complex and time-consuming. B-lines, in lung ultrasonography (LUS), could constitute an interesting tool for LVFP evaluation in clinical practice, although data regarding their association with invasive haemodynamics are lacking. The purpose of this study was to explore the diagnostic accuracy of B-lines in identifying elevated left ventricular end-diastolic pressure (LVEDP). Method and results: 81 adults with significant dyspnoea (NYHA ≥ 2) were prospectively analyzed by LUS in four areas in each hemithorax and a complete TTE within four hours prior to coronary angiography. Twenty-eight patients had elevated LVEDP. Clinical variables yielded a C-index of 79% to identify elevated LVEDP. The number of total B-lines was higher in the elevated LVEDP group (1.0vs17.0, p < 0.0001) and significantly increased the diagnostic accuracy (C-index increase = 10.5%, p = 0.002) and net reclassification index (NRI = 145.4, 113.0–177.9, p < 0.0001) on top of clinical variables. Conclusion: This study demonstrates the substantial diagnostic capacity of B-lines to identify elevated LVEDP, which appears superior to that of classical echocardiographic strategies. This tool should be considered in a multi-parametric approach in patients with heart failure. Highlights: ASE/EACVI recommendation for the estimation of left ventricular filling pressure is quite complex and time consuming. B-lines, in lung ultrasound, could constitute an interesting tool for LVFP evaluation in clinical practice, but data regarding their association with invasive hemodynamics are lacking. Clinical variables had a C-index of 79% to identify elevated LVEDP. Total B-lines number was higher in the elevated LVEDP group (1.0vs17.0, p < 0.0001) and significantly increased diagnostic accuracy (C-index increase = 15.5%, p = 0.004) and a net reclassification index (NRI = 142.0, 108.5–175.6, p < 0.0001) on top of clinical variables. In contrast, the 2016 ASE/EACVI recommendations did not significantly increase neither the reclassification nor the diagnostic accuracy. There is an important diagnostic capacity of B-lines to identify elevated filling pressure and that is probably something to consider in our clinical routine.